2013
DOI: 10.1093/pcp/pct166
|View full text |Cite
|
Sign up to set email alerts
|

The Thellungiella salsuginea Tonoplast Aquaporin TsTIP1;2 Functions in Protection Against Multiple Abiotic Stresses

Abstract: Examination of aquaporin (AQP) membrane channels in extremophile plants may increase our understanding of plant tolerance to high salt, drought or other conditions. Here, we cloned a tonoplast AQP gene (TsTIP1;2) from the halophyte Thellungiella salsuginea and characterized its biological functions. TsTIP1;2 transcripts accumulate to high levels in several organs, increasing in response to multiple external stimuli. Ectopic overexpression of TsTIP1;2 in Arabidopsis significantly increased plant tolerance to dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 72 publications
(101 reference statements)
1
67
0
3
Order By: Relevance
“…Nevertheless, the transgene also had beneficial effects on plant growth and fruit yield under both control and water stress conditions [8]. The overexpression of TsTIP1;2 enhanced tolerance to drought, salt and oxidative stresses in transgenic Arabidopsis [33]. These studies suggested that TIPs play an important role in controlling plant physiology both under normal and stress conditions.…”
Section: Introductionmentioning
confidence: 92%
“…Nevertheless, the transgene also had beneficial effects on plant growth and fruit yield under both control and water stress conditions [8]. The overexpression of TsTIP1;2 enhanced tolerance to drought, salt and oxidative stresses in transgenic Arabidopsis [33]. These studies suggested that TIPs play an important role in controlling plant physiology both under normal and stress conditions.…”
Section: Introductionmentioning
confidence: 92%
“…Evidence from numerous studies involving quantifying aquaporin expression and overexpression and/or down-regulation of aquaporin genes strongly supports a prominent role in increasing water permeability of different tissues in rice [36][37][38][39] and other plants [34,40,41]. However, the drought tolerance of transgenic plants overexpressing aquaporin genes varied where it increased in some cases [34,38,42] but was not affected or even decreased in some others [43,44].…”
Section: Introductionmentioning
confidence: 97%
“…Nonetheless, PIP1 aquaporins have been suggested to form heterotetramers with PIP2s with increased water transport activity [31,32]. Some aquaporins have been reported to transport other physiologically important small molecules such as CO 2 [33], boron or silicon [25] or H 2 O 2 [34].…”
Section: Introductionmentioning
confidence: 99%
“…Using the yeast model, H 2 O 2 transport ability of TsTIP1;2 was also confirmed. Thus, TsTIP1;2 might improve H 2 O 2 -mediated long-distance signal transfer which led to the induction of multiple stress tolerance (Wang et al, 2014). Besides TIPs, different PIPs have also been used to enhance plant's stress tolerance in different plants, such as banana (Musa spp.)…”
Section: Calcium and Reactive Oxygen Species/redox-mediated Signalingmentioning
confidence: 99%